Genetic Variation Assessment of Some Prunus Species Using Srap Markers - Sabrya, Sabrya J.; Ali, Avesta M.; Jubrael, Jaladet M. S. (Science Journal of University of Zakho, 2016)
Genetic variation at molecular level was evaluated among three species of Prunus genus and a wild species, (P. arabica (wild), P. argentea (wild), P. dulcis (local), and P. dulcis (wild ). The genetic variation assessment was carried out using SRAP molecular markers. The genetic similarity coefficient revealed the genetic relationship among the samples tested in which the highest genetic distance was between P. dulcis (local), and P. dulcis (wild), and lowest genetic distance was between P. arabica (wild), P. argentea (wild). The phylogenetic tree was obtained using UPGMA method depending on the total number of SRAP bands. There were two main groups in the dendrogram: the first one consists of two subgroup: P. arabica and P. argentea cluster together in one Subgroup and P. dulcis (wild) appear alone in this subgroup. P. dulcis (Local variety) appear in the second group alone.